Kappa opioid receptor antagonists: A possible new class of therapeutics for migraine prevention. (July 2017) - Xie, Jennifer Y; De Felice, Milena; Kopruszinski, Caroline M; Eyde, Nathan; LaVigne, Justin; Remeniuk, Bethany; Hernandez, Pablo; Yue, Xu; Goshima, Naomi; Ossipov, Michael; King, Tamara; Streicher, John M; et al.
Background: Stress is the most commonly reported migraine trigger. Dynorphin, an endogenous opioid peptide acting preferentially at kappa opioid receptors (KORs), is a key mediator of stress responses. The aim of this study was to use an injury-free rat model of functional cephalic pain with features of migraine and medication overuse headache (MOH) to test the possible preventive benefit of KOR blockade on stress-induced cephalic pain. Methods: Following sumatriptan priming to model MOH, rats were hyper-responsive to environmental stress, demonstrating delayed cephalic and extracephalic allodynia and increased levels of CGRP in the jugular blood, consistent with commonly observed clinical outcomes during migraine. Nor-binaltorphimine (nor-BNI), a long-acting KOR antagonist or CYM51317, a novel short-acting KOR antagonist, were given systemically either during sumatriptan priming or immediately before environmental stress challenge. The effects of KOR blockade in the amygdala on stress-induced allodynia was determined by administration of nor-BNI into the right or left central nucleus of the amygdala (CeA). Results: KOR blockade prevented both stress-induced allodynia and increased plasma CGRP. Stress increased dynorphin content and phosphorylated KOR in both the left and right CeA in sumatriptan-primed rats. However, KOR blockade only in the right CeA prevented stress-induced cephalic allodynia as well as extracephalic allodynia, measured in either the right or left hindpaws. U69, 593, a KOR agonist, given into the right, but not the left, CeA, produced allodynia selectively in sumatriptan-primed rats. Both stress and U69, 593-induced allodynia were prevented by right CeA U0126, a mitogen-activated protein kinase inhibitor, presumably acting downstream of KOR. Conclusions: Our data reveal a novel lateralized KOR circuit that mediated stress-induced cutaneous allodynia and increased plasma CGRP in an injury-free model of functional cephalic pain with features of migraine and medication overuse headache. Selective, small molecule, orally available, and reversible KOR antagonists are currently in development and may represent a novel class of preventive therapeutics for migraine.